INVESTMENT OF INSURANCE FUNDS AS AN ALTERNATIVE TO INFRASTRUCTURE FINANCING THROUGH GOVERNMENT AND PRIVATE COOPERATION IN THE MIDST OF COVID-19 PANDEMIC - Nabilla Fitra Larasati; Dina Aprilia; Dinda Bhawika Wimala Pastika; Ismi Aulia Wahyudi; Desya Annisa Anandita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The existence of covid-19 has an impact on the decline in the economy and investment to finance infrastructure in Indonesia. The government must maintain a favorable investment environment in the face of the covid-19 pandemic. This is essential in order to create a level playing field for investors. Insurance is one possibility to non-bank infrastructure financing; this is related to the insurance industry's ability to generate revenue during a pandemic due to increased public awareness of the significance of self-protection against high healthcare costs if exposed to the 19th plague. As a response, the government must aim to attract investors in the insurance business, who will eventually be engaged to create an alternative investment insurance fund for infrastructure development through a Public Private Partnership.